Construção de um biomodelo com interposição de placa oclusal para análise de tensões nos discos articulares da ATM pelo método dos elementos finitos - Silva, Carlos Augusto Gomes da (2016)
The aim of this study was to investigate the possibility of creating a three-dimensional model of the masticatory system of a patient for analysis in MEF. Also, to configure the parameters for the attainment of a clenching test with variations in intensities bite force with the interposition of two occlusal splints of different materials. Using the computed tomography (CT) and magnetic resonance imaging (MRI) of a patient, were built, through the process of reverse engineering, seven pieces to compose a biomodel. Four software was used throughout the process to achieve the desired result. Also, from this model was created finite element mesh of components and defined the boundary conditions. An occlusal splint was created and its physical and mechanical properties were switched to simulate the behavior of two different plates: a rigid and resilient. The model received force vectors that simulate the action of four pairs of muscles: temporal, masseter, medial pterygoid and lateral; and was assigned to these three distinct forces for each test: 25oN, 50oN and 75oN. According to what was found in this study it can be concluded that the construction of a biomodel from CT and MR images are completely feasible. In addition, the methodology used to obtain the models and the settings configured for the tests in MEF resulted in a good approach to clinical reality along the lines of current research.